Modern Historico-Pedagogical Literature on Kharkiv University Activities in the 19th-early 20th century - Kulysh, S. M. (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article provides historical and pedagogical viewpoint          on scientific literature ranging from the 1990-s to the beginning of the 21 century dedicated to the activity of Kharkiv University before the revolution, further development of pedagogics, considerable improvement in scientific and pedagogical staff training, introduction of methodological innovations into pedagogical activity.